OPTIMALISASI TATA KELOLA PARIWISATA DI DESA BURAI KABUPATEN OGAN ILIR - Fahlevi, Anggun Badriyansyah; Fahlevi, Arry Halbadika (Lentera Jurnal Manajemen, 2024)
Abstract The tourism sector in Indonesia is currently relied on as an alternative sector to boost the economy in Burai Village, Ogan Ilir Regency, because the sector that has been relied on, namely the agricultural sector, tends to experience stagnation, thus creating unemployment and poverty, therefore it is necessary to immediately optimize tourism governance in the village. Burai, Ogan Ilir Regency. This research aims to find out how to optimize tourism governance in Burai Village, Ogan Ilir Regency. The research method used is descriptive qualitative. The data collection method is a documentation method from secondary sources. The results of the research show that the optimization of tourism management in Burai Village is not optimal, this is because the road access to Burai Village is damaged so tourists who want to visit Burai Village experience difficulties so tourists are not comfortable traveling to Burai Village. Recommendations for Optimizing Tourism Governance in Burai Village, Ogan Ilir Regency must be carried out in collaboration with all policy stakeholders so that the determined objectives can be successful and effective.